Triathlon: an innovative approach in secondary school physical education - Machota Blas, V.E. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
This paper presents an innovative implementation of Triathlon in a school-based Physical Education context.  A teaching unit of Triathlon was designed to become part of the Physical Education Syllabus. It introduced adolescents to Triathlon fostering physical activity in the natural environment to stay active, healthy and fit. The results on the impact of the unit on students were studied through discussions with focus groups. Students seem to have become aware of the sport of Triathlon and demonstrate outcomes on knowledge, understanding and basic skills related to Triathlon. This unit has provided them the opportunities to learn these skills and practise this sport beyond school based Physical Education and increase their levels of physical activity. Its initial development may seem conditioned upon location and characteristics of very specific material, but with appropriate modifications it can be adapted and included in the school-based Physical Education Syllabus.